Crick, Watson y el ADN en 90 minutos - Strathern, Paul, 1940- (En 90 minutos., 2014)
Outlines the history of genetics and presents a snapshot of the lives and work of the scientists, Crick and Watson. Gives an explanation of the meaning and importance of DNA, and its implications for the twentieth century and beyond. Suggested level: secondary.